Игрушки: стихи / А. Барто ; худ. Н. Фаттахова - Барто Агния Львовна (ФЛАМИНГО, 2009)
Экземпляры: ПО (04.08.2009) / Инвентарный номер: 43884 / Цена: 65.00 / Авт.знак: Б 26 / ГРНТИ: 17.82.93 / ББК: 84 (2 Рос=Рус)6